1994
DOI: 10.1007/bf00313599
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia mitigates neuronal damage in the rat brain when initiated several hours following transient cerebral ischemia

Abstract: Intra-ischemic moderate hypothermia generally protects the brain against ischemic cell death, while hypothermia instigated several hours into the reperfusion phase is considered to be less effective. Here we report the effect of hypothermia (32.5 degrees - 33.5 degrees C) of 5-h duration, initiated at 2, 6, 12, 24 and 36 h into the recirculation phase following 10 min of transient cerebral ischemia, on ischemic neuronal injury in the hippocampus and striatum of the rat. Hypothermia induced at 2 h, and 6 h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(69 citation statements)
references
References 32 publications
3
64
0
2
Order By: Relevance
“…Postinsult hypothermia reduced infarct area, with longer periods of cooling providing progressively increased protection. Although this is in agreement with the results obtained in adult animals (25)(26)(27), studies using shorter periods of cooling in younger animals have shown contradictory results. Yager et al (18) observed no protection with postinsult hypothermia in the 7-d old rat; however, using the same model, Thoresen et al (28) found marked protection with 3 h of postinsult hypothermia.…”
supporting
confidence: 90%
“…Postinsult hypothermia reduced infarct area, with longer periods of cooling providing progressively increased protection. Although this is in agreement with the results obtained in adult animals (25)(26)(27), studies using shorter periods of cooling in younger animals have shown contradictory results. Yager et al (18) observed no protection with postinsult hypothermia in the 7-d old rat; however, using the same model, Thoresen et al (28) found marked protection with 3 h of postinsult hypothermia.…”
supporting
confidence: 90%
“…[2][3][4][5][6] However, most of these studies used a narrow time window, with Applying these data to clinical practice would suggest that induced hypothermia is beneficial only in the very first few hours after stroke onset. Several neurosurgical studies showed a positive effect of mild hypothermia on uncontrollable intracranial hypertension after severe head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis as a systemic response to infection was suspected, according to the criteria of the American College of Chest Physicians, when Ն2 of the following conditions became manifest: heart rate Ͼ90 bpm, white blood cell count Ͼ12 000 or Ͻ4000 cells/mm 3 , respiratory rate Ͼ20 breaths per minute, or PaCO 2 Ͻ32 mm Hg. Body temperature as 1 further point was not analyzed.…”
Section: Evaluation Of Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the required threshold may be modified by the severity of the initial insult, how soon hypothermia is started after the insult and how long cooling is continued. 99,100,107 There is an obvious trade-off between the adverse systemic effects of cooling, which increase markedly below a core temperature of 32-341C, and the potential cerebral benefit. The potential systemic adverse effects of hypothermia in newborn infants include increased mortality particularly in preterm infant, hypoglycemia, reduction of cardiac contractility and cardiac output, ventilation-perfusion mismatch, increased blood viscosity, coagulopathy, acid-base and electrolyte imbalance and an increased risk of infections.…”
Section: 105-108mentioning
confidence: 99%